use the laplace transform to solve the given system of differential equations. dx dt = −x y dy dt = 2x x(0) = 0, y(0) = 4

Respuesta :

Answer:

[tex]x(t)=\frac{4}{3}e^t-\frac{4}{3}e^{-2t}\\ \\y(t)=\frac{4}{3}e^{-2t}+\frac{8}{3} e^t}[/tex]

Step-by-step explanation:

Given:

[tex]\left \{ {{x'=-x+y} \atop {y'=2x}} \right.\\\\\text{With initial conditions:} \ x(0)=0 \ \text{and} \ y(0)=4[/tex]

Solve the system of differential equations using Laplace transforms.

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

(1) - Take the Laplace transform of each equation

[tex]\boxed{\left\begin{array}{ccc}\text{\underline{Laplace Transforms of DE's:}}\\L\{y''\}=s^2Y-sy(0)-y'(0)\\L\{y'\}=sY-y(0)\\L\{y\}=Y\end{array}\right}[/tex]

For equation 1:

[tex]x'=-x+y\\\\\Longrightarrow L\{x'\}=-L\{x\}+L\{y\}\\\\\Longrightarrow sX-0=-X+Y\\\\\Longrightarrow sX=Y-X\\\\\Longrightarrow \boxed{Y=sX+X} \rightarrow \text{Equation 1}[/tex]

For equation 2:

[tex]y'=2x\\\\\Longrightarrow L\{y'\}=2L\{x\}\\\\\Longrightarrow sY-4=2X\\\\\Longrightarrow \boxed{2X=sY-4} \rightarrow \text{Equation 2}[/tex]

Now we have the following system:

[tex]\left \{ {{Y=sX+X} \atop {2X=sY-4}} \right.[/tex]

(2) - Solve the system using algebraic techniques (i.e. substitution, elimination, etc..)

[tex]\text{Substituting equation 1 into equation 2: }\\\\\Longrightarrow 2X=s^2X+sX-4\\\\\Longrightarrow s^2X+sX-2X=4\\\\\Longrightarrow X(s^2+s-2)=4\\\\\Longrightarrow \boxed{X=\frac{4}{s^2+s-2}}[/tex]

(3) - Take the inverse Laplace transform

[tex]L^{-1}\{X\}=4L^{-1}\{\frac{1}{s^2+s-2}\}[/tex]

**One the RHS we will have to use partial fraction decomposition to break up the fraction.

[tex]\frac{1}{s^2+s-2} \Rightarrow \frac{1}{(s-1)(s+2)}\\\\\Longrightarrow [\frac{1}{(s-1)(s+2)}=\frac{A}{s-1} +\frac{B}{s+2}](s-1)(s+2)\\\\\Longrightarrow 1=A(s+2)+B(s-1)\\\\\Longrightarrow 1=As+2A+Bs-B\\\\\Longrightarrow0s+1=(A+B)s+(2A-B)\\\\\Longrightarrow \left \{ {{A+B=0} \atop {2A-B=1}} \right. \\\\\Longrightarrow \text{After solving the system we get:} \ \boxed{A=\frac{1}{3} \ \text{and} \ B=-\frac{1}{3} }[/tex]

Now we have:

[tex]L^{-1}\{X\}=\frac{4}{3} L^{-1}\{\frac{1}{s-1}\}-\frac{4}{3} L^{-1}\{\frac{1}{s+2}\}[/tex]

[tex]\boxed{\left\begin{array}{ccc}\text{\underline{Table of basic Laplace Transforms:}}\\1\rightarrow \frac{1}{s} \\t^n\rightarrow \frac{n!}{s^{n+1}}\\e^{at} \rightarrow\frac{1}{s-a}\\ \sin(at)\rightarrow\frac{a}{s^2+a^2}\\\cos(at)\rightarrow\frac{s}{s^2+a^2}\\e^{at}\sin(bt)\rightarrow\frac{b}{(s-a)^2+b^2}\\e^{at}\cos(bt)\rightarrow\frac{s-a}{(s-a)^2+b^2}\\t^ne^{at}\rightarrow\frac{n!}{(s-a)^{n+1}} \end{array}\right}[/tex]

[tex]L^{-1}\{X\}=\frac{4}{3} L^{-1}\{\frac{1}{s-1}\}-\frac{4}{3} L^{-1}\{\frac{1}{s+2}\}\\\\\Longrightarrow \boxed{\boxed{x(t)=\frac{4}{3}e^t-\frac{4}{3}e^{-2t}}}[/tex]

(4) - Repeat steps 2-3 to find y(t)

[tex]\text{Taking equation 2:} \ 2X=sY-4\\\\\Longrightarrow \boxed{X= \frac{sY-4}{2}} \ \text{Substitute this into equation 1}[/tex]

[tex]\Longrightarrow Y=s(\frac{sY-4}{2}})+\frac{sY-4}{2}}\\\\\Longrightarrow [Y=\frac{s^2Y-4s+sY-4}{2}]2\\\\\Longrightarrow 2Y=s^2Y-4s+sY-4\\\\\Longrightarrow s^2Y+sY-2Y=4s+4\\\\\Longrightarrow Y(s^2+s-2)=4s+4\\\\\Longrightarrow \boxed{Y= \frac{4s+4}{s^2+s-2}}[/tex]

[tex]L^{-1}\{Y\}=L^{-1}\{\frac{4s+4}{s^2+s-2}\}\\\\\Longrightarrow 4s+4=A(s-1)+B(s+2)\\\\\Longrightarrow 4s+4=As-A+Bs+2B\\\\\Longrightarrow 4s+4=(A+B)s+(-A+2B)\\\\\Longrightarrow \left \{ {{A+B=4} \atop {-A+2B=4}} \right. \\\\\Longrightarrow A=\frac{4}{3} \ \text{and} \ B= \frac{8}{3}[/tex]

[tex]L^{-1}\{Y\}=L^{-1}\{\frac{4s+4}{s^2+s-2}\}\\\\\Longrightarrow L^{-1}\{Y\}=\frac{4}{3} L^{-1}\{\frac{1}{s+2} \}+\frac{8}{3} L^{-1}\{\frac{1}{s-1} \}\\\\\Longrightarrow \boxed{\boxed{y(t)= \frac{4}{3}e^{-2t}+\frac{8}{3} e^t}}[/tex]

Thus, the system is solved.